Impact of Coronary Chronic Total Occlusion on Long-term Clinical Outcome in Patients with Unprotected Left Main Disease Undergoing Percutaneous Coronary Intervention - Imad Sheiban; Filippo Figini; Valeria Gaspartto; Claudio Moretti; Filippo Leonardo; Shaoliang Chen; Fabrizio D’Ascenzo (Cardiology Discovery)
Objectives:. Reported data regarding the prevalence, prognostic impact, and safety and efficacy of revascularization of coronary chronic total occlusion (CTO) in patients with left main coronary artery (LMCA) disease who undergo percutaneous coronary intervention (PCI) are scarce. The aim of the present study was to compare clinical outcomes among patients with LMCA disease undergoing PCI. Outcomes were compared between those with and without coronary CTO and between those with CTO who had successful and unsuccessful CTO recanalization procedures. Methods:. All consecutive patients with significant LMCA disease (>50% stenosis at coronary angiography) who underwent PCI between July 2014 and December 2018 were retrospectively included in our study. The primary endpoint of the study was long-term mortality. Secondary endpoints included the incidence of myocardial infarction, repeat percutaneous or surgical revascularization, stroke, and stent thrombosis. Results:. Between July 2014 and December 2018, 578 patients underwent PCI for LMCA disease at Pederzoli Hospital and University of Turin were enrolled. They were divided into 3 groups: group A: 374 (65%) patients without CTO, group B: 108 (19%) patients with untreated or unsuccessfully treated CTO, and group C: 96 (17%) patients with successfully treated CTO. At a median follow-up of (1090 ± 279) days, there were no statistically significant differences between the groups in terms of the primary and secondary endpoints. However, there was a trend towards higher mortality in patients with untreated or unsuccessfully treated CTO (13% vs. 19% vs. 14% in groups A, B, and C, respectively; P = 0.12). The primary and secondary endpoints were further analyzed based on the presence or absence of myocardial viability: subgroup C1: 54 (56%) patients with successful percutaneous transluminal coronary angioplasty (PTCA) having viability, and subgroup C2: 42 (44%) patients with successful PTCA not having viability. There was a trend toward a statistically significant higher rate of death among patients in group B, who underwent unsuccessful recanalization with viable myocardium (19% vs. 9% vs. 19% in groups B, C1, and C2, respectively, P = 0.05). On multivariable analysis, the propensity for successful revascularization of CTO was associated with a reduced risk of death (P = 0.01; odds ratio, 0.75; 95% confidence interval: 0.62–0.87). Conclusions:. Among patients with LMCA disease undergoing PCI, CTO represents a common finding associated with worse prognosis. Successful revascularization of CTO in patients with viable myocardium appears to significantly improve prognosis.